Valuing the effect sizes hypothesized in phase 3 trials of targeted therapies in oncology - Reilly, G; Wise, A; Attwood, S; Scudder, C; Love, S (BioMed Central, 2017)
This abstract was not included in this publication as it was already published. See Annals of Oncology, Volume 27, Issue suppl_6, 1 October 2016, 317P (10.1093/annonc/mdw366.02) - Oxford University Press.